The relationship between social support and the quality of working life of neonatal intensive care unit nurses in selected hospitals of Ahwaz University of Medical Sciences-2016 - Ghouligaleh, Mahnousheh; Shirinabadi Farahani, Azam; Alaee Karahroudy, Fatemeh Alaee Karahroudy; Pourhoseingholi, Mohamad Amin; Khanali Mojen, Leila (Advances in Nursing & Midwifery, 2018)
Abstract Introduction: Social support has a key role in improvement of quality of working life of nurses. The present study aimed at measuring the quality of nurse’s working life and perceived social support and examine their relationship in neonatal intensive care unit nurses. Methods: In the present descriptive-correlational study, the statistical population consisted of nurses working at neonatal intensive care units of selected hospitals affiliated to Ahwaz University of Medical Sciences, selected by census. Overall, 98 nurses were selected. Since the number of employed nurses was approximately the same, all nurses were selected by the census method and based on the inclusion criteria.Tools used included the "Demographic Questionnaire”, “Multidimensional Scale of Perceived Social Support" and "Quality of Nurses' Work Life". Validity of the questionnaires was confirmed by 12 experts, and its reliability was confirmed by the Cronbach's alpha coefficient. Data were analyzed using the SPSS-20 software. Results: The highest mean value in social support belonged to the "family" dimension (5.19± 1.05) and the lowest to "friends" (4.50± 1.11), and overall mean social support value was 4.78 ± 0.99. The quality of working life had the highest mean value in the "working life" dimension (3.67± 0.72) and the lowest in "personal life" (3.38± 0.89), and overall mean value of quality of working life was 3.57± 0.57 in nurses. The obtained results showed a positive correlation between social support and the quality of working life in nurses (r=0.25, P=0.02). Conclusions: The obtained results showed a significant and positive relationship between perceived social support and quality of nursing working life. However, the relationship between subscales of these two variables was mildly confirmed. Generally, the present study results are in accordance with the results of previous studies.